The Harder You Work, the Higher Your Satisfaction With Life? The Influence of Police Work Engagement on Life Satisfaction: A Moderated Mediation Model - Liu, Ting; Zeng, Xiaoqing; Chen, Meirong; Lan, Ting (Frontiers in Psychology, 2019)
Background: life satisfaction is a key component in quality of life and is associated with many factors, including occupation and family life. Results of existing studies examining associations among work engagement, work-family conflict, and life satisfaction have been inconsistent. Objective: we explored the mechanism of action of police work engagement on life satisfaction, and analyzed the relationships among work engagement, work-family conflict, psychological detachment, and police life satisfaction from the angle of family and work relationships. Methods: 760 police officers completed the work engagement scale, life satisfaction scale, work-family conflict scale, and psychological detachment scale; 714 questionnaires were valid. Results: work engagement not only directly affected police life satisfaction (β = 0.58, p < 0.001), but also influenced police life satisfaction through work-family conflict (β = -0.07, p < 0.05). Different levels of psychological detachment moderated not only the relationship between work engagement and work-family conflict (β = 0.17, p < 0.001), but also the relationship between work-family conflict and life satisfaction (β = 0.07, p < 0.05). Conclusion: a moderated mediation model was established. Work-family conflict partly mediates the relationship between work engagement and police life satisfaction. Psychological detachment moderates the first and second half of the mediating process in which work engagement affects police life satisfaction through work-family conflict.